Kenaf biomass as potential biopolymer - Mustafa Kamalbhrin, Mohd. Adlan; N. , Nuraisyah; Anuar, Hazleen; Mel, Maizirwan; Seeni Mohamed, Nurhafizah; Mohd. Nasir, Nur Aimi (2011)
This research was made to synthesis polylactic acid (PLA) from kenaf biomass that is currently waste of kenaf fibre production. This project is carried out to aim in reducing the manufacturing cost of PLA, reducing market price of PLA and to sustain the green technology. Basically, the pre treatment process was done previously on kenaf biomass with sulfuric acid (H2SO4) to hydrolyze the cellulose content. The step is then continued with the fermentation process to obtain lactic acid using Rhizopus oryzae followed by the lactic acid separation and purification before it is further synthesized into PLA. The characteristic of treated and untreated kenaf biomass were tested by Fourier Transform Infrared (FTIR), X-Ray Diffractometer (XRD) and also Scanning Electron Microscopy (SEM) analysis.